High-Precision Object Detection Using 8 Proximity Sensors: Integration of Switching Algorithm and Visual Display - Sutarsi Suhaeb; Ahmad Risal; Andi Rakhmat Baharuddin (Program Studi Teknik Komputer, 2025)
This study developed an object detection system based on 8 proximity sensors implemented in a line follower robot using a switching algorithm. The system is controlled by an Arduino Nano microcontroller and displays detection results on a 16x2 LCD. The switching method is employed to read the sensors alternately, thereby reducing channel interference and lowering power consumption without compromising reading speed. Each sensor is calibrated with a predefined threshold to convert analog readings into digital signals, which are then visualized as icons or underscore symbols on the display. This research follows an experimental approach involving hardware design, microcontroller programming, and direct testing on a robotic track. The system was tested in five different track position scenarios. The results show that the system consistently and responsively detects objects. The switching method proved effective in improving reading efficiency and enhancing the robot’s navigation stability for accurate line following..